Effects of time perspective and self-control on psychological distress : a cross-sectional study in an Argentinian sample - Germano, Guadalupe (2021)
Fil: Germano, Guadalupe. Pontificia Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro de Investigaciones en Psicología y Psicopedagogía; Argentina